THE DIMENSION OF HISTORY IN THE NEO-SCHOLASTIC CONCEPTION OF EUROPEAN INTEGRATION - Šiaudvytienė, Elena (Politologija, 2013)
The article aims at analyzing the dimension of history in the neo-scholastic conception of the European integration. The research focuses on R. Schuman’s vision of the European integration. He was among the politicians who created the first European communities. His political thought was deeply influenced by the philosophy of the famous French philosopher J. Maritain and the pope Pius XII who both cherished the historical ideal of the European integration, based on the Christian philosophy of history. The main incentive for undertaking this kind of research was the wish to find an alternative intellectual and theoretical position that would not be based on the historicist principles of modernity and enlightenment. Eventually, such position could enhance the poor reflectivity of today`s European integration theory. The analysis of the neo-scholastic European unification idea revealed that all three authors grounded their understanding of history in onto-existential epistemology of Thomism. Its main claim is twofold. First, every historical moment is perceived as a reference to the underlying reality that is not dependent upon historical flow and endows it with spiritual meaning. Second, at the very moment of perceiving the temporal circumstances and grasping their underlying transcendental reality, the moral requirements for the concrete historical moment are discovered. J. Maritain, Pius XII, and R. Schuman withdrew their ideas of European unification and Christian heritage of Europe from this Thomistic conception of history and the onto-existential epistemology. It is sustained that the results of the undertaken analysis can open qualitatively new theoretical perspectives in the European integration theory and thus help to create a more meaningful Europe. First of all, such a non-historicist position of looking at the process of European integration can provide one condition that is necessary for every true scientific enquiry: it can help to create a theoretical distance among the knowing subject and the known reality. Second, the Christian conception of a human person, which was held by J. Maritain, Pius XII, and R. Schuman, is able at least to stimulate the raising of the most fundamental questions about the true nature and goals of European unification. Third, the analysis has demonstrated that the issue of the Christian heritage of Europe is important and cannot be ignored, because it is a historical fact and not only a lofty idea.